Strengthening Public Relations Strategies of the Undergraduate Program in Early Childhood Islamic Education at IAIN Pontianak - Handes Handes (Program Studi Pendidikan Islam Anak Usia Dini, Institut Agama Islam Negeri Pontianak, 2026)
The development of digital technology encourages higher education institutions to adapt with innovative communication strategies in the management of public relations. The Early Childhood Islamic Education (PIAUD) study program at IAIN Pontianak faces challenges in building academic branding because the public relations activities carried out are still merely informative. This study aims to analyze the public relations strategies implemented by the PIAUD study program at IAIN Pontianak and to provide innovative recommendations for strengthening academic branding. The research method used is qualitative, with data collection techniques through observation, interviews, and documentation. Data analysis is conducted by including data condensation, data presentation, and conclusions as well as verification. The results of this study indicate that Instagram functions as a promotional medium for academic and social activities, while the website serves as an information tool that displays identity, vision-mission, curriculum, and the scientific works of lecturers and students. Nevertheless, the management is still less than optimal due to the absence of a public relations team, and the content displayed is still limited to information dissemination. The implications of these findings contribute to strengthening the theoretical perspective on public relations in higher education with an interactive and participatory approach. [Perkembangan teknologi digital mendorong Perguruan Tinggi untuk beradaptasi dengan strategi komunikasi yang inovatif dalam pengelolaan public relations. Program Studi Pendidikan Islam Anak Usia Dini (PIAUD) IAIN Pontianak menghadapi tantangan dalam membangun branding akademik karena aktivitas public relations yang dilakukan masih sebagai sarana informative. Penelitian ini bertujuan untuk menganalisis strategi public relations yang dilaksanakan oleh program studi PIAUD IAIN Pontianak serta memberikan rekomendasi inovatif dalam penguatan branding akademik. Metode penelitian yang digunakan adalah kualitatif dengan teknik pengumpulan data melalui observasi, wawancara, dan dokumentasi. Analisis data dilakukan dengan meliputi kondensasi data, penyajian data, dan simpulan serta verfikasi. Hasil penelitian ini menunjukkan bahwa instagram berfungsi sebaga media promosi aktivitas akademik dan sosial sedangkan website berperan sebagai sarana informasi yang menampilkan identitas, visi-misi, kurikulum, karya ilmiah dosen dan mahasiswa. Walaupun demikian, pengelolaan tersebut masih kurang optimal karena belum terbentuknya tim public relatios dan konten yang ditampilkan masih terbatas pada penyampaian informasi. Implikasi dari temuan ini adalah berkontribusi pada penguatan perspektif teoritis mengenai public relations di Perguruan Tinggi dengan pendekatan interaktif dan partisipatif.]